"Violence. Enough already": findings from a global participatory survey among women living with HIV. Issue 6 (1st December 2015) - Orza, Luisa; Bewley, Susan; Chung, Cecilia; Crone, E Tyler; Nagadya, Hajjarah; Vazquez, Marijo; Welbourn, Alice
Abstract : Introduction: Women living with HIV are vulnerable to gender‐based violence (GBV) before and after diagnosis, in multiple settings. This study's aim was to explore how GBV is experienced by women living with HIV, how this affects women's sexual and reproductive health (SRH) and human rights (HR), and the implications for policymakers. Methods: A community‐based, participatory, user‐led, mixed‐methods study was conducted, with women living with HIV from key affected populations. Simple descriptive frequencies were used for quantitative data. Thematic coding of open qualitative responses was performed and validated with key respondents. Results: In total, 945 women living with HIV from 94 countries participated in the study. Eighty‐nine percent of 480 respondents to an optional section on GBV reported having experienced or feared violence, either before, since and/or because of their HIV diagnosis. GBV reporting was higher after HIV diagnosis (intimate partner, family/neighbours, community and health settings). Women described a complex and iterative relationship between GBV and HIV occurring throughout their lives, including breaches of confidentiality and lack of SRH choice in healthcare settings, forced/coerced treatments, HR abuses, moralistic and judgemental attitudes (including towards women from key populations), and fear of losing child custody. Respondents recommended healthcare practitioners and policymakers address stigma and discrimination, training, awareness‐raising, and HR abuses in healthcare settings. Conclusions: Respondents reported increased GBV with partners and in families, communities and healthcare settings after their HIV diagnosis and across the life‐cycle. Measures of GBV must be sought and monitored, particularly within healthcare settings that should be safe. Respondents offered policymakers a comprehensive range of recommendations to achieve their SRH and HR goals. Global guidance documents and policies are more likely to succeed for the end‐users if lived experiences are used.